Modification and Characterisation of Vanadium Phosphorus Oxide Catalysts for Selective Oxidation of Propane to Acrylic Acid - Saw, Chaing Shen (2006)
Vanadium phosphate catalysts synthesized via VOPO4∙2H2O were further reduced in isobutanol to produce VOHPO4∙0.5H2O precursor. Calcination of this precursor in propane/air environment (1% propane in air) transformed into activated (VO)2P2O7 catalysts. The morphology, structure, oxidant’s nature and catalytic performance for propane oxidation to acrylic acid over this catalyst strongly depended on the duration of calcination. The catalyst calcined for 36 h (VPD36P) exhibits low surface area. However, prolonged calcination promoted a higher surface area with better crystallization. VIII and VV phases are detected in all catalysts. The SEM micrographs showed that all propane/air catalysts gave rosebud type agglomerates with various sizes but in a uniform shape.